Usefulness of Shirodhara in the Management of Hyperactive Children - Anpuchelvi, S.; Sritharan, G. (Unit of Siddha medicine, University of Jaffna, Sri Lanka, 2014)
Attention Deficit Hyperactive Disorder is a neurobehavioral disorder of childhood period and characterized by inattention, impulsiveness and hyperactivity. AK case control study was conducted in children with ADHD. Children for the present study were included from Herbal Health Care Centre, Jaffna from the period on 01.01. 2013 – 28.02.2013. Children between 6 to 15 years were considered for study. 48 children were registered, out of which 8 children discontinued the treatment. Grouping of patients- Selected children were randomly divided into four groups, keeping in mind that all the four groups children from various grades(classes), schools & socio economic strata. All four groups (Group A,B,C& D) were having 12 childern administered with Vallarai khiritha, Vallarai khiritha + shirodhara, placebo, placebo + shirodhara respectively. Pre-assessment screening of ADHD children was done according to Criteria. Subjects aged 6-15 years of either Sex. Children with average / normal IQ level with their Diagnostic card were included in this study. Children with physical disability, Children with psychiatric illness, Children with gross brain damage causing mental retardation, Children with any genetic disorder and Unreliable history were excluded from the study. Doses were according to the body weight of the child (200 mg/ kg / day) in 2 divided doses for 3 months. Children were called for follow up every fortnightly. Any discomfort or untoward serious side effects were noticed. After 3 months of treatment, the tests were re-administered. Effect of the therapy was assessed on the basis of improvement. This study indicates the synergistic effect of shirodhara with the study drug. Further extensive study is needed to authenticate the results of the present study, with larger samples.
Keywords: Attention Deficit Hyperactivity Disorder (ADHD); Impulsivity; Reaction time; Shirodhara